Preparation and characterization of graphene paper for electromagnetic interference shielding. (February 2015) - Zhang, Lu; Alvarez, Noe T.; Zhang, Meixi; Haase, Mark; Malik, Rachit; Mast, David; Shanov, Vesselin
Abstract: Syntheses of multifunctional structures, both in two-dimensional and three-dimensional space, are essential for advanced graphene applications. A variety of graphene-based materials has been reported in recent years, but combining their excellent mechanical and electrical properties in a bulk form has not been entirely achieved. Here, we report the creation of novel graphene structures such as graphene pellet and graphene paper. Graphene pellet is synthesized by chemical vapor deposition (CVD), using inexpensive nickel powder as a catalyst. Graphene pellet can be further processed into a graphene paper by pressing. The latter possesses high electrical conductivity of up to 1136 ± 32 S cm −1 and exhibits a breaking stress at 22 ± 1.4 MPa. Further, this paper-like material with thickness of 50 μm revealed 60 dB electromagnetic interference (EMI) shielding effectiveness.